MORINGA OLEIFERASEBAGAI MAKANAN PENDAMPING ASI PADA BALITA STUNTING - Urwatil Wusqa Abidin; Andi Liliandriani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2021)
Specific nutrition intervention efforts for short children under five are focused on the 1,000 First Day of Life (HPK) group. Consuming Moringa Oliferadi Polewali Mandar Regency is one of the efforts taken to accelerate the growth and development of toddlers because it is found in abundance of nutrients, such as: vitamin A, vitamin C, calcium, and iron. This research is expected to be an alternative for families with stunting toddlers in order to provide adequate nutritional intake by utilizing Moringa Olifera. This research uses a Quasi Experimental design, which is an experiment that has treatment, impact measurement, experimental units but does not use random assignments to create comparisons. in order to infer changes caused by treatment. The design used was one group pre test and post test design, which is a study by comparing the nutritional status of toddlers before the intervention and after the intervention. The results showed that the Sig. (2-tailed) both variables equal to 0.000. This value is <0.05, so it can be concluded that there is an effect of giving Moringa Oliferar powder on body weight (BW) and height (TB) of toddlers. Because of this, giving Moringa Olifera powder, can increase BW and TB in toddlers.